PEMBAHARUAN SISTEM PEMIDANAAN, KHUSUSNYA PIDANA PENJARA (STUDI KEMASYARAKATAN) - Beggy Tamara; Dadi Waluyo; Sumardi Sumardi; Sukhebi Mofea (SUPREMASI HUKUM, 2022)
Most of the criminal law reforms outside the Criminal Code currently use a special minimum criminal threat as an instrument of punishment. The formulation of the problem that will be discussed in this study is as follows, How to create a pattern of punishment that is not oriented to the mere imposition of imprisonment and does not cause problems in its application? The conclusion is that imprisonment is still considered effective in preventing and fostering criminals, but it is time for us to think about making policies that are not oriented only to the imprisonment of perpetrators. According to the author's suggestion, law enforcement officers must be more courageous in taking a stand regarding restorative justice efforts, prosecutors and judges have also begun to dare to impose demands and decisions whose criminal threats are in the form of alternatives. Legislators must apply the bottom-up principle in the preparation of criminal legislation. Keywords: Criminal System Reform, Imprisonment